High-lipid nutritional environment in different ontogenetic periods induce developmental programming of rat prostate at aging - Scarpelli, Tatiane Pereira [UNESP]; Pytlowanciv, Eloisa Zanin [UNESP]; Pinto-Fochi, Maria Etelvina [UNESP]; Taboga, Sebastião Roberto [UNESP]; Góes, Rejane Maira [UNESP] (Oxford University Press (OUP), 2023)
Maternal obesity and high-fat diet (HFD) affect permanently prostate histophysiology in adulthood, but the consequences during aging are unknown. Here, we evaluated the prostate alterations in middle-aged rats subjected to a high-lipid nutritional environment (HLE) in different ontogenetic periods. Wistar rats (56 weeks of age) were assigned into groups exposed to standard nutrition (C) or HLE during gestation (G), gestation and lactation (GL), from lactation onward (L), from weaning onward (W) and from gestation onward (AL). HLE in the periods after weaning consisted of HFD (20% fat), and during gestation and lactation it also included previous maternal obesity induced by the HFD. HLE increased total cholesterol and triglyceride levels in all groups and led to insulin resistance in GL and AL and obesity in L. Serum testosterone levels decreased ~67% in GL, ~146% in L and W, and ~233% in AL. Histological and stereological analysis revealed an increment of the stromal compartment and collagen fibers in the prostates of all HLE groups, as well as degenerative lesions, such as cell vacuolation and prostate concretions. HLE aggravated acinar atrophy in G, GL, and L, and in AL it reached more than 50% of the prostate area for most animals. The foci of prostatic intraepithelial neoplasia increased in AL. Tissue expression of androgen receptor did not vary among groups, except for a higher stromal expression for G and GL. Even when restricted to gestation and lactation, HLE induces diffuse acinar atrophy in the aging prostate and worsens degenerative and premalignant lesions when it continues throughout life.